Layanan Bimbingan Belajar bagi Anak Berkebutuhan Khusus: Studi Kualitatif Fenomenologis di Yayasan Pendidikan Tumbuh Kembang Talenta Kudus - Sucipto, Ade; Asya, Fadhila; Anggraini, Cindy Aulia; Mutriana, Fani (Jurnal Bimbingan dan Konseling Pandohop, 2026)
Children with Special Needs (ABK) are children who, in their growth and development processes, experience differences compared to their peers, whether physically, intellectually, emotionally, socially, or behaviorally. This study aims to describe tutoring services for children with special needs at the Talenta Kudus Growth and Development Education Foundation. A qualitative phenomenological approach was employed, focusing on exploring teachers’ experiences in providing services to ABK students. The research informants consisted of one guidance teacher who served as the sole educator directly responsible for delivering tutoring services at the foundation. Data collection was conducted from October to November 2025 through in-depth interviews, participatory observation, and documentation. The findings indicate that tutoring services for children with special needs at the foundation are implemented in an individualized and flexible manner, oriented toward each child’s unique needs. The implementation integrates the principles of the Merdeka Curriculum, which allows for differentiated learning, and aligns with the Inclusive Curriculum, which emphasizes access, acceptance of diversity, and the provision of support according to students’ needs. The tutor plays a central role in designing learning strategies, creating a supportive learning environment, and maintaining intensive communication with parents. This study underscores the importance of a personal, empathetic, and adaptive approach in tutoring services for children with special needs, as well as the need for institutional support to strengthen professional practices in the field.